Public Health and Yellow Fever during the constitutional debate in 1812 - Hernández Villalba, Pepa (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
This article deals with the debate on Public Heath in the Cádiz Cortes (parliament) in the period up to the enactment of the Constitution in 1812. Underlining the key role of yellow fever played in this process, it pursues two lines of argument: reopening the dialogue between Health and Politics at a critical point in Spanish History and examining the attempts to create a coherent body of sanitary legislation as well as the elements that impeded the process.
Keywords: Public health; Health code; Epidemy; Yelow fever; Cádiz Cortes; Constitution